IMPLEMENTASI STRATEGI CONTEXTUAL TEACHING AND LEARNING (CTL) PADA MATA PELAJARAN MATEMATIKA KELAS 1A DI MIS AT-TAQWA SAMBASTAHUN AJARAN 2023-2024 - Urva Afina; Yayan Ridwan, Muhammad Asyura (Adisam Publisher, 2026)
The aim of this research is to describe: 1) Contextual Teaching and Learning (CTL) strategy steps in Class IA Thematic Subjects at MIS At- Taqwa Sambas 2) Implications of Contextual Teaching and Learning (CTL) Strategies in Class 1A Mathematics Subjects at MIS At-Taqwa Sambas, 3) supporting and inhibiting factors in implementing the Contextual Teaching And Learning (CTL) Strategy in Class 1A Mathematics Subjects at MIS At-Taqwa Sambas. This research uses a qualitative approach and phenomenological research type. The results of the research show that 1) The steps of the Contextual Teaching and Learning (CTL) strategy in Class 1A Mathematics Subjects at MIS At- Taqwa Sambas are in accordance with the process of constructivism, finding, asking, learning communities, models, reflection and final assessment 2) There is an impact of using the Contextual Teaching and Learning Strategy Learning (CTL) in Mathematics class IA at MIS At- Taqwa Sambas which is related to contextual learning components, namely establishing meaningful relationships, doing meaningful work, carrying out self-regulated learning processes, collaborating, thinking critically and creative, providing individualized services, striving to achieve high standards, and using authentic assessments 3) Supporting factors are students, the learning environment and learning media, while inhibiting factors are students and implementation time for implementing the Contextual Teaching And Learning (CTL) Strategy In Class 1A Mathematics Subjects at MIS At-Taqwa Sambas.